Development of a Method to Measure and Compare Hospital Waste: The Premier Hospital Waste Index. (January 2014) - Lowe, Timothy J.; Kroch, Eugene; Martin, John; Bankowitz, Richard
The authors developed 15 measures and a comparative index to assist acute care facilities in identifying and monitoring clinical and administrative functions for health care waste reduction. Primary clinical and administrative data were collected from 261 acute care facilities contained within a database maintained by Premier Inc, spanning October 1, 2010, to September 30, 2011. The measures and 4 index models were tested using the Cronbach α coefficient and item-to-total and Spearman rank correlations. The final index model was validated using 52 facilities that had complete data. Analysis of the waste measures showed good internal reliability (α = .85) with some overlap. Index modeling found that data transformation using the standard deviation and adjusting for the proportional contribution of each measure normalized the distribution and produced a Spearman rank correlation of 0.95. The waste measures and index methodology provide a simple and reliable means to identify and reduce waste and compare and monitor facility performance.